Medidas de Eficiência Energética na IP - José Miguel Gonçalves Cerqueira de Oliveira (2018)
The objective of this dissertation is the study, analysis and definition of measures of efficiency in Public Lighting (PL). A description of the historical evolution of IP was initially made, and some examples of projects were presented. Next, the evolution of lighting technologies for IP was presented, with special emphasis on contemporary technologies. LED technology was analyzed in particular, presenting its main characteristics, advantages and disadvantages A chapter was dedicated to the description of some control and management systems of PL networks currently used, presenting their main characteristics. Subsequently, the project of Public Lighting of a road made was presented. For the lighting study carried out, two proposals for solution of lighting implementation are presented, using two different technologies: LED technology and high pressure sodium vapor. The two alternatives were compared and their pros and cons were analyzed, namely the energy efficiency level, in order to find the most appropriate solution to the case under study. In the annex, some of the main lighting parameters required to execute a lighting project in a suitable way are described Key words: Energy Efficiency, LED, Lighting, High Sodium vapor bulbs, Public Lighting.